PENGARUH PENERAPAN PBL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 2 PADANG PANJANG TAHUN PELAJARAN 2018/2019 - Uswantun Hasanah (Departemen Matematika, 2019)
with conventional learning and describe the development of students' mathematical problem solving skills during the PBL model implementation. This type of research is quasi-experimental with the Static Group Design research design. Based on the results of data analysis, it was concluded that the mathematical problem solving skills of students who learn to use the PBL model are better than students who learn with conventional learning in class VIII SMPN 2 Padang Panjang. Then, the development of students' mathematical problem solving skills during the PBL model has increased.Keywords – Mathematical Problem Solving, Problem Based Learning Model, Conventional Learning